1997
DOI: 10.1128/jb.179.23.7274-7279.1997
|View full text |Cite
|
Sign up to set email alerts
|

The TolB protein interacts with the porins of Escherichia coli

Abstract: TolB is a periplasmic protein of the cell envelope Tol complex. It is partially membrane associated through an interaction with the outer membrane lipoprotein PAL (peptidoglycan-associated lipoprotein), which also belongs to the Tol system. The interaction of TolB with outer membrane porins of Escherichia coli was investigated with a purified TolB derivative harboring a six-histidine tag. TolB interacted with the trimeric porins OmpF, OmpC, PhoE, and LamB but not with their denatured monomeric forms or OmpA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 26 publications
3
73
0
Order By: Relevance
“…This requirement for native disorder is undoubtedly a consequence of the colicin cellular uptake mechanism because the narrow lumen of an OmpF monomer is thought to be the entry point for the unfolded polypeptide into the periplasm before translocation across the OM (19). Thereafter, association with TolB would be expedited because OmpF is known to be closely associated with Tol proteins (34). The role of native disorder in colicin translocation is further illustrated by the pore-forming colicin N, which uses OmpF both as a receptor and translocator to the periplasm where the toxin binds TolA.…”
Section: Resultsmentioning
confidence: 99%
“…This requirement for native disorder is undoubtedly a consequence of the colicin cellular uptake mechanism because the narrow lumen of an OmpF monomer is thought to be the entry point for the unfolded polypeptide into the periplasm before translocation across the OM (19). Thereafter, association with TolB would be expedited because OmpF is known to be closely associated with Tol proteins (34). The role of native disorder in colicin translocation is further illustrated by the pore-forming colicin N, which uses OmpF both as a receptor and translocator to the periplasm where the toxin binds TolA.…”
Section: Resultsmentioning
confidence: 99%
“…Because the exact function is not known, current research focuses on the link between Tol-Pal proteins and porins, lipopolysaccharides (LPS), or O-antigen biogenesis. It has been shown that the central domain of the TolA protein, as well as the TolB protein, interacts in vitro with major OM trimeric porins such as OmpF, OmpC, LamB, and PhoE in the presence of sodium dodecyl sulfate (150,554). TolA and TolB do not interact with OmpA or the OM denaturated porins.…”
Section: Tol-dependent Colicinsmentioning
confidence: 99%
“…That is the case for the Braun's (murein) lipoprotein (Lpp) ; the peptidoglycan-associated lipoprotein (PAL) (Lazzaroni & Portalier, 1992) ; the periplasmic protein TolB ; and the inner-membrane complex formed by TolQ, TolR and TolA proteins (Lazzaroni et al, 1999). A series of studies have provided evidence for the existence of large complexes containing these proteins that establish a physical link between the inner and the outer membrane (Bouveret et al, 1995(Bouveret et al, , 1999Rigal et al, 1997 ;Clavel et al, 1998 ;Lazzaroni et al, 1999). This function is essential for providing stability and integrity to the cell envelope.…”
Section: Abbreviationsmentioning
confidence: 99%